Jurnal Penyuluhan: Adopsi Teknologi Petani pada Sekolah Lapangan Pengelolaan Tanaman Terpadu (SL-PTT) - Karmila Muchtar, Djoko Susanto, Ninuk Purnaningsih (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Field School of Comprehensive Agriculture Land-Use Management (SL-PTT) is agriculture innovation from ministry of agriculture. The SL-PTT program aims accelerating the adoption of innovation at the farm level to increase production in a sustainable manner.